Biomarkers for kidney involvement in pediatric lupus. (June 2015) - Goilav, Beatrice; Putterman, Chaim; Rubinstein, Tamar B
Lupus nephritis (LN), the renal involvement in systemic lupus erythematosus, is currently diagnosed by histopathology obtained by percutaneous renal biopsy and is associated with increased morbidity and mortality in both adults and children. LN is more prevalent and severe in children, requiring aggressive and prolonged immunosuppression. The consequences of the diagnosis and its treatment have devastating long-term effects on the growth, well-being and quality of life of affected children. The paucity of reliable clinical indicators of the presence and severity of renal involvement have contributed to a halt in the reduction of progression to end-stage renal disease in recent years. Here, we discuss the recent development of biomarkers in the management of LN and their role as therapeutic targets.